Study Report of the Socio-Economic Development of Himalayan Hills - Planning Commission (Planning Commission, 1982)
The task force for the study of economic development in the Himalayan region of India, constituted by the Planning Commission, Government of India, decided in its deliberations that for the sake of convenience few study groups should be formed for preparing the reports of the task force. Accordingly the Planning Commission in its notification I.D. Note PO(P)19/1/HIM/MIP-81 dated 28-8-1981 formed two study groups.
Planning Commission, Government of India